STUDENTS’ PERCEPTION ON THE SPEAKING PERFORMANCE IN THE CLASSROOM AT THE EIGHTH GRADE OF SMPN 1 KUINDRA - Rizki Noramalia; melda yeni; Sri Erma Purwanti (Program Studi Pendidikan Bahasa Inggris, 2024)
The problem of this research was the Eighth- grade students of SMPN 1 Kuindra got problem while they speak in front of the class. It is assumed that their perception of their speaking performance is the cause of this problem . Therefore, the purpose of this research is to know “students’ Perception on the Speaking Performance in the classroom at the Eighth Grade of SMPN 1 Kuindra”. This research was descriptive quantitative research. The researcher was distributing questionnaire to 31 respondents to answer the purpose above. The sample was taken by using saturated sampling, because the sample is limited. After collecting the data, the researcher found that students’ perception on speaking performance is in good level. It can be interpreted that, most of students of the eighth-grade of SMPN 1 Kuindra perhaps can become a good speaking performers. It means not only good or bad perception can influence students’ speaking but also some other factors.